Pulmonary function in preoperative, postoperative and post hospital discharge after heart surgery: controlled clinical study - Soares, Jully Wendy; Santos, Gabriela Xavier; Ferreira, Monica Beatriz; Foresti, Bruno Bonfim; barbosa, Danillo; Ferreira, Viviane Cristine (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Cardiac surgery may influence respiratory function at different times, such as before and after surgery, and after hospital discharge. Objective: Evaluate the respiratory functionality (respiratory muscle strength and peak expiratory flow-PEF) of pre, postoperative and post-hospital discharge of cardiac surgery patients at a Regional Hospital in the south of Minas Gerais. Methods: The sample consisted of 11 subjects: 6 women (54.4%) and 5 men (45.46%), with mean age of ± 60 years. The mean height, weight and BMI were respectively: ±1.61m, ±71.08kg and ±26.89. Results: The values of the functional variables were lower than expected; men had the highest values of maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP) and PEF at the 3 moments; there was correlation rs < 1 p < 0.01 of PRE MIP and POS MIP; PRE MIP and POS MEP; third day MIP and PRE MIP; and POS MEP and PRE MEP. Conclusion: men had the highest values of respiratory functional variables. The analysis of the variables at the 3 moments showed that after hospital discharge most of them reduced their values. The post hospital discharge should be a concern of professionals assisting cardiac surgery patients.